PERLINDUNGAN HUKUM TERHADAP KONSUMEN PENGGUNA PARFUM ISI ULANG YANG TIDAK MENCANTUMKAN LABEL KOMPOSISI DI KOTA PEKANBARU - Dumai Putra Mulia Pasaribu; Maryati Bachtiar; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Along with the era of free trade, nowadays various types of cosmetics are circulating in the market with various uses from various brands as well. Cosmetic products, which are the result of the development of the pharmaceutical industry, have now developed into one of the basic needs of the community along with the development of people's lifestyles. Business actors are competing to produce various kinds of beauty products with various uses for the community to attract as many consumers as possible . Human desire to always look more beautiful, beautiful and perfect. There is still a sale of refill perfume in Pekanbaru City that does not include this composition label, which can endanger consumers in using the refill perfume. The dangers arising from using this refill perfume can cause irritation to the skin with perfume levels that are not in accordance with what has been set by the BPOM besides that it can also cause inflammation of the skin cells so that it can cause skin cancer.The problems that the authors make the basis for in this study are how legal protection for consumers related to the use of refill perfumes that do not include composition labels in the city of Pekanbaru and how are business actors responsible for refill perfume products that do not include composition labels in the city of Pekanbaru.This type of research can be classified into the type of empirical or sociological research, because in this study the author directly conducts research at the location or place under study in order to provide a complete and clear picture of the problem under study. This research was conducted in Pekanbaru CityThe results of this study are first. Protection for consumers related to the sale of cosmetic products without material composition regulated in the UUPK is contained in Article 4 letter c. The right to information is important for consumers, because with information consumers can choose the desired product and avoid losses due to misuse of the product. Providing information is also an obligation of business actors as regulated in Article 7 letter b. In addition to protection through rights and obligations, protection of consumers can also be protected by actions that are prohibited by business actors as regulated in Article 8 letter IUUPK. Second, responsibility is the obligation of business actors if consumers feel disadvantaged. Regarding the responsibilities of business actors regulated in Article 19 UUPK. Business actors can be responsible by providing compensation in the form of refunds or replacement of goods.Keywords: Consumers, Business Actors, Refill Perfume